Computer science principles : the foundational concepts of computer science for AP computer science - Hare, Kevin (Atlanta, GA : Yellow Dart Publishing, 2020)
Computer Science Principles introduces the creative side of computing. Once you've made your way through this book, you'll be editing photos, designing websites, coding JavaScript, and getting organized with spreadsheets$1 (Band along the way you'll learn the foundational concepts of computer science.s
1 - Hardware, Software, Number Systems, and Boolean Expressions -- 2 - Pixels, Images, and Adobe Photoshop -- 3 - Compressing Data -- 4 - Storing Data: Spreadsheets and Databases -- 5 - Protecting Data: Heuristics, Security, and Encryption -- 6 - The Internet -- 7 - Web Design: HTML and CSS -- 8 - Programming: JavaScript -- 9 - Impact of Computing.
Keywords: COMPUTER SCIENCE